Senteurs de miel et d'encens: le benjoin a Java centre - Goloubinoff, M. (1998)
Sumatra benzoin (Styrax spp.) is a fragrant resin that has been traded overseas for many centuries. However, more than 70% of the production is sent from Sumatra to Java where it is used as an ingredient in traditional cigarettes and as incense in rituals. In Southern Central Java several small factories specialise in 'klembak menyan' cigarettes which are made from tobacco, Chinese rhubarb (Rheum officinale) and benzoin. This hand rolled cigarette was popular until the late 70s when the kretek cigarette became a serious competitor. However, the product still has customers among transmigrants, Central Java countrymen and low-income workers. The incense market, as a benzoin outlet, is far more important. Javanese people still use incense in many rituals, despite changing life habits and fundamental Islam influence. Several factories manufacture incense by mixing benzoin with other raw materials. Java remains the main place for incense use although some is exported or sent to other Indonesian islands such as Bali.